MAMPUKAH PROFITABILITAS DAN FEE AUDIT MEMPENGARUHI INTEGRITAS LAPORAN KEUANGAN PERUSAHAAN? - Ferry Christian; Vierly Ananta Upa; Arifuddin Mannan; Aini Indrijawati (ITB AAS INDONESIA, 2023)
The company's financial statements are a disclosure of information and management's responsibility for the fairness of financial management. For this reason, financial reports are required that are fair, valid and free from manipulation. The integrity of financial reports is prepared based on generally accepted accounting principles, which provide information that is true, reliable and understandable to users in making decisions. This study aims to analyze the factors that affect the integrity of a company's financial statements, namely audit fees and profitability. The method used is quantitative and data analysis with multiple linear regression. The data source in this study is secondary data, namely the company's annual reports that have been published on the Indonesia Stock Exchange. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2020 period. The sampling method used in this study was purposive sampling.The number of samples in this study were 39 companies. The results of the study show that profitability has no effect on the integrity of financial statements, while audit fees have a significant effect on the integrity of financial statements.